ANALISIS PENGUATAN UMKM DAN DAMPAKNYA BAGI PEREKONOMIAN NASIONAL SEBAGAI UPAYA MENGATASI DAMPAK COVID-19 - Dahiri (Pusat Kajian Anggaran, 2020)
Corona virus has had a negative impact on the world economy, including Indonesia. In Indonesia this can be seen from the reduction in workers in both the formal and informational sectors. The beating of the national economy has had an impact on macro and UMKM businesses. Eventhough UMKM has an important role in increasing national economic growth. But before the outbreak, UMKM themselves had problems in developing their businesses, namely regulations that were not integrated, export performance was low, and difficulty in accessing capital.This research uses quantitative methods and multiple regression models with the Cobb-Douglas production function. The results of the study concluded that UMKM had a significant impact in boosting the national economy. Whereas in terms of employment, only UMK have a significant impact on employment. Based on these results, efforts must be made by the government to strengthen UMKM. First, capital must be centered on one institution. Second, the government must provide incentives or subsidies for exports. Third, access to capital and incentives must be contained in regulations in the form of laws.